Pemberian Pupuk Organik Cair dan Pupuk P Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Adinda Sari Surbakti; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research am to determine the effect of interaction of liquid organic fertilizer and P-fertilizer along with teh best combination in cleasing the growth and yield of onion plant (Allium ascalonicum L.). The research was conducted at experimental garden of agriculture facully, universitas riau in ovtober to desember 2018 and done in factorial form 4 x 3 using completely randomized design (CRD). The first factors was liquid organic fertilizer NASA and consist of 4 levels that are 0 m.l-1, 7 m.l-1, 8 m.l-1, and 9 m.l-1. The second factor was P fertilizer and consist of 3 levels that are 0 kg.ha-1, 150 kg.ha-1, 200 kg.ha-1.The bservasin parameters were plant height, number of leaves per clump, number of tubers per clump, tuber diameter per clump, weight of fresh tubers and weight of worth keeping tubers. The data werw analyzed using analysis of varriance and followed by duncan’s new multiple range test (DNMRT) at level 5 %. The result of the research showed that the treatment of liquid organic fertilizer have non-significant effect on all observation parameter. The combination treatment of liquid organic fertilizer 9m.l-1 and P fertilizer 0 kg.ha-1 to give the best result in creasing weight of fresh tubers and weight of worth keeping tubers. Keywords : onion plant, liquid organic fertilizer NASA, P fertilizer